1998
DOI: 10.1152/jn.1998.80.1.255
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rapid Stopping During Human Walking

Abstract: The mechanisms involved in rapidly terminating human gait were studied. Subjects were asked to walk at a comfortable speed and to stop walking as soon as they felt an electrical stimulus to the superficial peroneal nerve. This simulated hitting an obstacle with the top of the foot. Stimuli were presented repeatedly at random during a 20-min period of walking. Electromyograms and joint angular movements of the right leg and forces under both feet were recorded. The step cycle was divided into 16 parts, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
95
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 14 publications
10
95
1
Order By: Relevance
“…Another limitation was that only outcome variables in the last step were assessed. Although most deceleration occurs in this step [7,22,23], other studies have shown important adjustments in the trailing limb in the step prior to termination, namely a decrease in push-off GRF [5,8,9,11]. Finally, due to technical limitations the data of leading limb preference, temporal variables and joint angles were collected in different runs than the GRF and COP data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another limitation was that only outcome variables in the last step were assessed. Although most deceleration occurs in this step [7,22,23], other studies have shown important adjustments in the trailing limb in the step prior to termination, namely a decrease in push-off GRF [5,8,9,11]. Finally, due to technical limitations the data of leading limb preference, temporal variables and joint angles were collected in different runs than the GRF and COP data.…”
Section: Discussionmentioning
confidence: 99%
“…For safe gait termination, forward movement of the body has to be slowed down to achieve a stable upright position [2,5]. In able-bodied persons the leading limb, which is the limb that stands still first, is mainly responsible for the production of the necessary braking ground reaction force (GRF).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, very little is known about the adaptation of the dorsiflexor muscles during ageing (Obata et al 2010). However, these muscles play an important role in locomotion (Ceccato et al 2009;Hase and Stein 1998;Zehr and Stein 1999) by lifting the foot during the swing phase and preventing tripping. They are also involved in postural responses to stance perturbations (Nardone et al 1995;Stelmach et al 1989) and unexpected slips during walking Woollacott 1998, 1999).…”
Section: Introductionmentioning
confidence: 99%